Relationship Between the Loaded Pressure and Flow Rate of Packed Red Blood Cells and Various Infusion Solutions in Normal Infusion Lines and Catheters. (November 2021) - Miyoshi, Hirotsugu; Nakamura, Ryuji; Noda, Yuko; Kimura, Hiroshi; Kamiya, Satoshi; Morio, Atsushi; Watanabe, Tomoyuki; Narasaki, Soushi; Toyota, Yukari; Saeki, Noboru; Tsutsumi, Yasuo M.
Abstract : BACKGROUND: We investigated the relationship between the loaded pressure and flow rate in various catheters and the entire infusion line including the catheters, in several infusion solutions and packed red blood cells. METHODS: We connected the infusion line and catheter to the infusion solution and used an outer pressure bag or a compressor to pressurize the infusion solution bag to a pressure within the clinical (up to 450 mm Hg) or higher range (up to 1050 mm Hg). We approximated the relationship between the loaded pressure and flow rate in the entire infusion line including the catheter, versus the catheter alone, as a power function and compared the power numbers. RESULTS: In the clinical pressure range of normal saline, the power numbers of the entire infusion line for the 24-, 22-, 20-, and 18-gauge catheters were 0.76, 0.82, 0.81, and 0.86, respectively, while those for the catheter alone were 0.67, 0.63, 0.56, and 0.44, respectively. In the higher pressure range of normal saline, the power numbers of the entire infusion line for the 24-, 22-, 20-, and 18-gauge catheters were 0.68, 0.70, 0.71, and 0.73, respectively, while those for the catheter alone were 0.62, 0.61, 0.59, and 0.58, respectively. As the power number of the entire infusion line was closer to 1.00 than the values of the catheter, the relation between the loaded pressure and the flow rate was more linear in the entire infusion line than that in the catheter. Similar results were obtained using packed red blood cells and 40% glycerin mixture in normal saline. CONCLUSIONS: Regardless of the type of infusion solution or transfusion, the pressure-flow relationship in the catheter was nonlinear and not directly proportional. However, within the clinical pressure range (up to 450 mm Hg), the relationship between the flow rate and pressure in the entire infusion line was almost linear and proportional.